Actualization of Religious Moderation Values for Students at State Islamic University in Indonesia - Muhammad Sholeh (Indonesian Academy of Social and Religious Research (IASRR), 2023)
Indonesia is a pluralistic country and has much plurality. With this plural, it seems to be a